The Immigrant Next Door - Bursztyn, Leonardo; Chaney, Thomas; Hassan, Tarek A.; Rao, Aakaash (American Economic Review, 2024)
We study how decades-long exposure to individuals of a given foreign descent shapes natives’ attitudes and behavior toward that group. Using individualized donations data, we show that long-term exposure to a given foreign ancestry leads to more generous behavior specifically toward that group’s ancestral country. Focusing on exposure to Arab Muslims to examine mechanisms, we show that long-term exposure (i) decreases explicit and implicit prejudice against Arab Muslims, (ii) reduces support for policies and political candidates hostile toward Arab Muslims, (iii) increases charitable donations to Arab countries, (iv) leads to more personal contact with Arab Muslims, and (v) increases knowledge of Arab Muslims and Islam. (JEL D64, D83, D91, J15)